Coaching and Collaborative CPD; its impact on teachers’ attitudes towards professional development and their professionalism in an international school - O'Rahilly, Frank (2017)
The following research aims to identify the impact collaborative learning opportunities, such as peer coaching, have on teachers’ attitudes towards continuing professional development (CPD) initiatives and their own professionalism. The research is carried out in an international school in the United Arab Emirates which has its own unique challenges and opportunities. The research is qualitative and used individual interviews and focus groups with teachers from a variety of cultural backgrounds and years of experience. The results show that incorporating collaborative learning into school led CPD initiatives can have a positive effect on teachers’ attitudes. However, what the research also uncovered was that circumstances outside the control of the study, such as the corporate management model and budgetary cutbacks had a greater impact on these teachers’ attitudes than the success of the collaborative learning.